Obstetric emergencies in a humanitarian context at the Somine Dolo hospital in Mopti, Mali - Seydou, Fane; Amadou, Bocoum; Soumana, Traore O.; Ibrahima, Kante (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Conflicts are a barrier to physical and financial access to health centers. Our objective was to evaluate obstetric emergencies in a humanitarian context at the Sominé DOLO hospital in Mopti. Methods: This was a descriptive and prospective longitudinal study from January to September, 2020 in the obstetrical gynecology department of the Sominé DOLO hospital in Mopti. Our objective was to evaluate obstetric emergencies in the humanitarian context. Results: The frequency of patients evacuated was 30.61%. The average age of the patients was 27 years with extremes of 15 and 49 years. Hemorrhage during pregnancy was the main cause of reference with 23.83%. The ambulance was the most used means of transport with 51%. Delay in evacuation was observed in 31.33 cases. About 73.03% of our patients had given birth by caesarean section. We recorded 64 maternal deaths, a rate of 10.67%. Fetal mortality in our study was 23.28%. Attacks by armed groups had a negative impact on the referral/evacuation system. Conclusions: The health system had experienced severe challenges due to insecurity. Armed conflicts were the cause of evacuation delays. Haemorrhage during pregnancy was the main reference cause. Maternal and perinatal mortality was high.